2015
DOI: 10.1002/oby.21224
|View full text |Cite
|
Sign up to set email alerts
|

A randomized clinical trial of a weight loss maintenance intervention in a primary care population

Abstract: Objective: In-person weight loss maintenance visits have been shown to reduce weight regain after initial weight loss. This study examined, in a primary care population, whether in-person visits plus portion-controlled meals were more effective in reducing 12-month weight regain than mailed materials plus portioncontrolled meals. Methods: Study participants (n 5 106) received 6 months of intensive behavioral treatment. Participants who completed this phase (n 5 84) were then randomized to continue monthly in-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 25 publications
0
8
2
Order By: Relevance
“…In adults, Tsai et al . showed that continued in‐person visits during the weight loss maintenance phase led to greater weight loss than contact by mail. Focus groups among children to study what strategies would be helpful in facilitating maintenance of weight loss post‐intervention brought forward that maintenance intervention contacts should be scheduled, personalized rather than automated, and with a familiar member of the intervention team .…”
Section: Discussionmentioning
confidence: 99%
“…In adults, Tsai et al . showed that continued in‐person visits during the weight loss maintenance phase led to greater weight loss than contact by mail. Focus groups among children to study what strategies would be helpful in facilitating maintenance of weight loss post‐intervention brought forward that maintenance intervention contacts should be scheduled, personalized rather than automated, and with a familiar member of the intervention team .…”
Section: Discussionmentioning
confidence: 99%
“…Patients typically do not report additional improvements in HRQOL when acute weight loss ends, after approximately 6 to 9 months, and weight loss maintenance (WLM) begins. Maintaining weight loss is widely known to be less innately rewarding than losing weight . Moreover, following completion of a high‐intensity lifestyle intervention, individuals with obesity are vulnerable to weight regain, which may be associated with deterioration in HRQOL (and cardiovascular disease risk factors) .…”
Section: Introductionmentioning
confidence: 99%
“…Several trials have demonstrated the efficacy of interventions explicitly designed to improve weight loss maintenance ( Jakicic, Marcus, Lang, & Janney, 2008 ; Perri et al, 2001 ; Perri et al, 2008 ; Svetkey et al, 2008 ; A. G. Tsai, Felton, Wadden, Hosokawa, & Hill, 2015 ; Wing, Tate, Gorin, Raynor, & Fava, 2006 ). Most weight loss maintenance trials to date have included a weight loss program first followed by a testing weight loss maintenance intervention(s).…”
mentioning
confidence: 99%
“…Several trials have demonstrated the efficacy of interventions explicitly designed to improve weight loss maintenance (Jakicic, Marcus, Lang, & Janney, 2008; Perri et al, 2001; Perri et al, 2008; Svetkey et al, 2008; A. G. Tsai, Felton, Wadden, Hosokawa, & Hill, 2015; Wing, Tate, Gorin, Raynor, & Fava, 2006).…”
mentioning
confidence: 99%